Potensi Metabolit Sekunder pada Salacca zalacca, Sonchus arvensis, and Carica papaya terhadap Aedes aegypti L. - Raden Roro Upiek Ngesti Wibawaning Astuti; Auliya Nur Illahi; Wali Nasir Saddiqi Umri; Afghan Azka Falah (Jurnal Penelitian Pendidikan IPA, 2023)
Dengue infection is still as a major public health in the world including Indonesia, wherein from January to June showed about 45,387 cases and 432 deaths. There are many prevention and control activities that have been carried out but have not given contented results despite using insecticides. Plants secondary metabolites are confirmed have biological activity and can protecting the plants from an insect pest and diseases. This study proposed that secondary metabolites in several plants have the potential as biolarvicide. This study aimed to determine the potency of secondary metabolites in Salacca zalacca, Sonchus arvensis, and Carica papaya as biolarvicide. Each extract was test in five concentrations of treatment and two controls, negative control using aquadest and positive control using temephos 1%. The third instar larvae of Ae. aegypti mosquito were used in biolarvicide test, with 10 larvae for each treatment and 3 replications for 24 hours. This study revealed that C. papaya extract showed the highest potency as biolarvicide compared to S.Â  zalacca and S. arvensis. The LC50 and LC90 for 24 hours of C. papaya extract were 2.62% and 5.49% respectively.